PENGARUH PROFITABILITAS DAN SOLVABILITAS TERHADAP HARGA SAHAM PERUSAHAAN TERINDEKS LQ45 DI BEI - Yuniar Fitriyani (STIE Mandala Jember, 2022)
The purpose of this study was to analyze the effect of independent variables, profitability proxied by Return On Equity (ROE) and solvency proxied by Debt to Assets Ratio (DAR) on the dependent variable, namely stock prices. The population in this study were 45 companies in the LQ45 category listed on the Indonesia Stock Exchange. Sampling in this study using purposive sampling method, namely as many as 31 companies that are consistently indexed LQ45 on the Indonesia Stock Exchange (IDX) during the 2015-2019 period with the amount of data processed after the outlier process as many as 129 samples. The analysis test model used in this hypothesis is multiple linear regression analysis. The results showed that profitability (ROE) had no effect on stock prices, solvency (DAR) had no effect on stock prices, and simultaneously (ROE) and solvency (DAR) had no effect on company stock prices. Keywords: Stock Price, Return on Equity (ROE), Debt to Assets Ratio (DAR)